2020
DOI: 10.1096/fj.201900738rr
|View full text |Cite|
|
Sign up to set email alerts
|

Association between maternal omega‐3 polyunsaturated fatty acids supplementation and preterm delivery: A proteomic study

Abstract: Maternal nutrition during pregnancy influences offspring health. Dietary supplementation of pregnant women with (n-3) long-chain polyunsaturated fatty acids (PUFA) was shown to exert beneficial effects on offspring, through yet unknown mechanisms. Here, we conducted a dietary intervention study on a cohort of 10 women diagnosed with threatened preterm labor with a nutritional integration with eicosapentaenoic and docosahexaenoic acids. Microvesicles (MV) isolated form arterial cord blood of the treated cohort … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

2
0
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 49 publications
2
0
0
Order By: Relevance
“…Our results align with those from Jamilian et al who found that n-3 FA supplementation was associated with decreased oxidative stress levels in women with gestational diabetes [17]. Finally, although not directly related, this evidence is also consistent with studies that have examined associations between prenatal n-3 FA supplementation and cord blood or neonatal oxidative stress levels [45][46][47][48]. Animal studies have also observed that maternal n-3 FA supplementation is associated with lower levels of oxidative stress biomarkers in placenta and offspring [42][43][44][49][50][51][52][53][54].…”
Section: Discussionsupporting
confidence: 92%
“…Our results align with those from Jamilian et al who found that n-3 FA supplementation was associated with decreased oxidative stress levels in women with gestational diabetes [17]. Finally, although not directly related, this evidence is also consistent with studies that have examined associations between prenatal n-3 FA supplementation and cord blood or neonatal oxidative stress levels [45][46][47][48]. Animal studies have also observed that maternal n-3 FA supplementation is associated with lower levels of oxidative stress biomarkers in placenta and offspring [42][43][44][49][50][51][52][53][54].…”
Section: Discussionsupporting
confidence: 92%
“…Human studies showed that higher levels of n-3 LCPUFA were associated with reduction in neonatal oxidative stress, reduced production of inflammatory leukotriene B4, and altered T-cell function [9,10]. Inverse correlations between n-3 LCPUFA levels and neonatal T-cell cytokine production were also reported, consistent with data of adult studies showing reduction of T-cell cytokine production with fish oil supplementation [9,11].…”
Section: Introductionsupporting
confidence: 63%